2015
DOI: 10.1007/s40596-015-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of a Culturally Tailored Short Film in Modifying Dementia Stigma Among Chinese Americans: A Pilot Study

Abstract: Chinese Americans still perceive severe dementia stigma. Nevertheless, a culturally tailored short film demonstrated promising impact in modifying stigma toward dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…A recent study has found that although Chinese Americans hold misconceptions about dementia, their lack of knowledge does not reflect a lack of desire to become further educated about this medical condition [ 3 ]. Moreover, other recent studies have demonstrated that Chinese Americans are becoming more receptive to e-health and to obtaining dementia knowledge using the Internet than before [ 11 - 13 ]. In 2014, Google occupied 69% of the global search engine market and was the most popular search engine in the United States [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has found that although Chinese Americans hold misconceptions about dementia, their lack of knowledge does not reflect a lack of desire to become further educated about this medical condition [ 3 ]. Moreover, other recent studies have demonstrated that Chinese Americans are becoming more receptive to e-health and to obtaining dementia knowledge using the Internet than before [ 11 - 13 ]. In 2014, Google occupied 69% of the global search engine market and was the most popular search engine in the United States [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although a single member in a family might be diagnosed with dementia, the disease burden often extends to the entire family. Because of a belief that dementia is the result of retribution for past sins committed by the family, both patients and their families often express feelings of shame if diagnosed with the disease . In order to minimize the delay in accessing care so that appropriate treatment and care plans can be initiated as early as possible, negative perceptions of the disease must be minimized among Chinese Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over 60% of respondents failed to recognize that dementia can shorten life expectancy after onset . In order to target stigma, ethnic media in the form of radio and short film could be important means of educating and informing Chinese immigrants. Existing research has provided some insight into the relationships between dementia, stigma and family history of dementia.…”
Section: Introductionmentioning
confidence: 99%